Efficacy of sources and application mode of micronutrients on dry matter accumulation, productivity of wheat and residual organic carbon status in sandy loam soil - SINGH, ANAND; SHAHI, U. P.; DHYANI, B. P.; KUMAR, ASHOK; KUMAR, SATENDRA; ., VIVEK; SINGH, PRASHANT DEO; SINGH, AKANSHA (Journal of Soil and Water Conservation, 2021)
The application of NPK for crop production is not quite enough for higher and quality crop production as well as soil health so balance fertilization with combination of macro and micronutrients application is much important. Selection of suitable nutrient sources, quantity, method and time of application are equally important to get higher yield with maintaining soil quality and environment. Considering this point, a field experiment was conducted following the 4R Nutrient Stewardship to evaluate the effect of different sources of micronutrients (Zn, Mn and B) fertilizers and their mode of application along with NPK on wheat crop during rabi season of 2017–18 and 2018–19 at the Crop Research Centre, Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, Uttar Pradesh, India. The maximum dry matter accumulation at each sampling interval was found with RDF + soil application of Zn HEDP + MnSO4+ Colemanite with the highest grain (4.25 t ha-1), straw (5.89 t ha-1) and biological yield (10.14 t ha-1), followed by RDF + foliar application of Zn HEDP + EDTA Mn + DOT. The application of RDF + foliar application of Zn HEDP + EDTA Mn + DOT resulted in a highest harvest index (HI) 42.18. Organic carbon, essential factor for soil conservation was also maximum with application of RDF + soil application of Zn HEDP + MnSO4 + Colemanite during both years while. The foliar application of any single micronutrient with RDF improved the parameters considerably over RDF.